Determination Of Risk Factors Of Musculoskeletal Disorders In Palm Oil Harvesting Workers In Batu Jong-Jong Village - Br.SK, Dea Ananda; Arrazy, Syafran; Peralihan, Hotmatua; Wasiyem; Utami, Tri Niswati (Universitas Ahmad Dahlan, 2025)
Background : Musculoskeletal disorders (MSDs) describe disorders of the musculoskeletal system that arise from exposure to static position pressure that is repeated over a long period of time. This condition often causes complaints in the joints, ligaments, and tendons, a condition that is commonly experienced by workers who harvest oil palm fruit. The purpose of this study was to identify the determination of risk factors (work posture, work duration, age, physical fitness, work period and body mass index (BMI)) for the occurrence of musculoskeletal disorders in oil palm fruit harvesters in Batu Jong-Jong Village. Methods: This study applies a cross-sectional design with the use of primary data as the main source. A total of 68 oil palm harvesters were selected as respondents through a Stratified Sampling technique. Data were collected using a questionnaire distributed to respondents, as well as the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM) assessment methods. The data obtained were then analyzed using the Chi-Square statistical test. Results: The results of the study showed that there was a relationship between work posture (p-value 0.003 and PR 2.172), age (p-value 0.000 and PR 3.095), physical fitness (p-value 0.009 and PR 2.160), length of service (p-value 0.009 and PR 2.160) with the incidence of musculoskeletal disorders. While there was no relationship between the duration of work (p-value 0.287 and PR 1.290) and body mass index (BMI) (p-value 0.936 and PR 1.076) with the incidence of musculoskeletal disorders. Conclusion: It can be concluded that there is a relationship between work posture, age, length of service and physical fitness with the incidence of musculoskeletal disorders in oil palm fruit harvesters.